In Vitro and InSilico Evaluation of 2-(1H-Benzo[d]imidazol-2-yl)-3-(4-(piperazin-1-yl)phenyl)propanenitrile as Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors - Sarita, K.; Kumar, N.; Agrawal, A.; Mali, S. N.; Sharma, S. (Russian journal of bioorganic chemistry, 2024)
Objective: Advanced cancer treatment is based on targeted therapy, providing greater precision while mitigating common drug toxicity and resistance. Recently, protein kinases have gained prominence as valuable subjects for cancer therapy. Methods: To investigate the anticancer potential of benzimidazole analogues, various derivatives of 2-(1H-benzimidazol-2-yl)-3-(4-(4-substituted-piperazin-1-yl)phenyl)propane nitriles ( IIa–IIj ) were synthesized. All the synthesized analogues were characterized through TLC, melting points, FT-IR, 1 H NMR, 13 C, and mass spectroscopy. The anticancer potential of synthesized analogues was determined through the sulforhodamine B (SRB) assay against lung carcinoma cell lines (A549) and % growth inhibition was determined using Dalton’s lymphoma ascites cells. A molecular docking study was performed against epidermal growth factor receptor tyrosine kinase (a selective target for inhibitors of cancer) to illustrate the binding modes of ligands in the EGFR target. Results and Discussion: In vitro cytotoxic studies revealed that derivatives ( IIh ) and ( IIa ) showed promising anticancer activity. Conclusions: It is concluded from in vitro and in silico studies that compound ( IIh ) showed significant a significant anticancer activity.